Assessing Contentment with Life among Nursing Students at Private Nursing Institute Karachi, Pakistan : Assessing Contentment with Life among Nursing Students - Nawaz, Haq; Gulzada, Muhammad; Islam, Muhammad; Bibi, Afsha; Khaliq, Fazal; Khan, Muhammad Abbas; Fazlullah, . (Pakistan Journal of Health Sciences, 2024)
Life contentment denotes the measure to which an individual finds joy in their life, encompassing contemplative reflections and constituting an element of overall happiness and self-well-being. Objective: To assess levels of contentment with life among nursing students. Methods: This cross-sectional study was conducted at a private nursing institute in Karachi, Pakistan, from October to December 2023. Additionally, a convenient sampling technique was used, with a total of ninety-eight student participants included in the study. Results: 98 participants reveal a predominantly young group (84% aged 18-24) with balanced gender distribution (49% male, 51% female) and diverse education levels (30% 1st year, 29% 2nd year, 16% 3rd year, 25% 4th year). Contentment levels varied (6.1% low, 37.8% moderate, 56.1% high). Demographic analysis showed no significant age differences based on gender or education years (p > 0.05). This comprehensive overview informs understanding of nursing student well-being. Conclusions: Most participants reported high life contentment, with no significant age differences based on gender or education years. Overall, the findings offer valuable insights into the well-being of nursing students, emphasizing the role of diverse demographics.